Students’ learning style and its effect on blended learning, does it matter? - Nurasma’ Shamsuddin; Jasber Kaur (International Journal of Evaluation and Research in Education (IJERE), 2020)
Blended learning is an approach in education system that provides multi delivery mode to optimize learning outcome and cost of program delivery in institutions. Little is known on how impactful blended learning in terms of achieving the desired learning outcome. This is because students’ learning style has influenced their achievement and if mediated in a hybrid learning environment like blended learning will further result in evaluation and performance of blended learning environment. This study aims to investigate learning styles among the students and their relationship with perceptions of blended learning. The study involved 119 students taking the course of Diploma in Information Technology at a private university. The learning style of the students was determined by using Kolb's Learning Style Inventory, while perceptions of blended learning were investigated using elements of process, content, and usability. Student perceptions on blended learning were assessed using a one-way ANOVA to determine the correlation with the learning style of the students. Majority of the students belong to the Convergent category, followed by Divergent, Accommodator, and Assimilator. The outcomes of this study showed no meaningful difference between students’ learning styles and their perceptions towards blended learning. The findings from the study could benefit academician in designing more suitable material according to students' preferred mode such as more hands-on tasks for Convergent groups, which belief, can improve the student's achievement.